2016
DOI: 10.1186/s12967-016-1080-9
|View full text |Cite
|
Sign up to set email alerts
|

Culture expansion of adipose derived stromal cells. A closed automated Quantum Cell Expansion System compared with manual flask-based culture

Abstract: BackgroundAdipose derived stromal cells (ASCs) are a rich and convenient source of cells for clinical regenerative therapeutic approaches. However, applications of ASCs often require cell expansion to reach the needed dose. In this study, cultivation of ASCs from stromal vascular fraction (SVF) over two passages in the automated and functionally closed Quantum Cell Expansion System (Quantum system) is compared with traditional manual cultivation.MethodsStromal vascular fraction was isolated from abdominal fat,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 32 publications
0
57
0
Order By: Relevance
“…The overall aim was to establish a logistically and clinically applicable off‐the shelf stem cell treatment strategy for patients. We changed from autologous to allogeneic cells, and we implemented a more standardized and reproducible stem cell production platform using semi‐automated closed bioreactor systems instead of flasks and human platelet lysate instead of fetal bovine serum, as well as cryo storage of a ready‐to‐use product .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall aim was to establish a logistically and clinically applicable off‐the shelf stem cell treatment strategy for patients. We changed from autologous to allogeneic cells, and we implemented a more standardized and reproducible stem cell production platform using semi‐automated closed bioreactor systems instead of flasks and human platelet lysate instead of fetal bovine serum, as well as cryo storage of a ready‐to‐use product .…”
Section: Discussionmentioning
confidence: 99%
“…The overall aim was to establish a logistically and clinically applicable off-the shelf stem cell treatment strategy for patients. We changed from autologous to allogeneic cells, and we implemented a more standardized and reproducible stem cell production platform using semi-automated closed bioreactor systems instead of flasks and human platelet lysate instead of fetal bovine serum, as well as cryo storage of a ready-to-use product [7][8][9][10][11][12][13][14][15][16][17][18][19]. We have in the present study demonstrated that it is feasible to generate a reproducible, standardized, and clinically applicable cell product from healthy donors that is safe and has a very promising efficacy profile.…”
Section: Discussionmentioning
confidence: 99%
“…Purity, differentiation capacity (adipose, bone, cartilage), and full phenotyping consistent with ISCT/IFATS standards for the ASC phenotype as well as genomic stability has been determined during manufacturing process development . Stability studies have been established, and currently 24‐month stability demonstrating sterility, viability, recovery, ASC immunophenotype, and cell potency as defined by in vitro cell adherence and proliferation, after thawing of the final product, has been documented and approved by competent authorities.…”
Section: Methodsmentioning
confidence: 99%
“…The shear forces in fixed bed reactors are low (~0.5 × 10 −5 N/cm 2 ) and consistent throughout the reactor with no peaks near the impeller; the shear forces also remain constant at all scales [81]. The in vitro expansion of MSCs has been reported in several types of fixed bed reactors [82][83][84][85]. One of the major drawbacks of fixed bed and other reactor types compared to stirred tank reactors is the challenge of efficient harvesting.…”
Section: The Expansion Of Mscs In Bioreactorsmentioning
confidence: 97%